Reverse short channel effects in nMOSFETs - Lee, Teck Koon. (2008)
Rapid advancement of the Metal-Oxide-Semiconductor (MOS) transistor in the last two decades has seen the approach of the 0.18um technology. However, this has caused phenomena that had not been previously observed. Two of these are the Reverse Short Channel Effects (RSCE) and the Transient Enhanced Diffusion (TED). The Reverse Short Channel Effects is the anomalous increase in the threshold voltage of devices as channel lengths are reduced and the latter is the enhanced diffusion of the implanted dopants following rapid thermal annealing.